NASSCOM : is it time to introspect and reinvent? - Karthik, D.; Upadhyayula, Rajesh ([London] : SAGE, 2016)
The case traces the genesis of NASSCOM and presents a decision situation faced by the new president who has to formulate a road map in the light of changed circumstances. NASSCOM has been an exemplary trade association. However, it faces challenges that can jeopardize the future if the industry. While the challenges do not have a short-term effect on the growing Indian IT-BPO industry, as the active industry ally, NASSCOM's new leader has to ensure long-term success of the IT-BPO industry. The case can be best used to understand the IT industry dynamics through the eyes of an exemplary trade body and also understand how a trade association in emerging economies can play an important role to fill institutional voids.
Originally Published in: D. K., & Upadhyayula, R. (2014). NASSCOM: Is it time to introspect and reinvent? BP0368. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; National Association of Software and Service Companies (New Delhi, India); Managerial economics -- Case studies; Computer software industry -- India -- Case studies